Electrostatic agglomeration of fly ash particles for hybrid gas cleaning devices. (October 2019) - Sobczyk, A T; Jaworek, A; Marchewicz, A; Krupa, A; Czech, T; Sliwiński, Ł
Abstract: The paper presents experimental results of the investigation of agglomeration of PM2.5 fly ash particles with larger particles in an electrostatic agglomerator. SEM micrographs of the obtained agglomerates shown that a single particle of the size of 10-20 μm can collect more than 20-50 PM2.5 particles in this type of agglomerator. The experiments were carried out in a semi-industrial scale channel of a cross section of about 600 mm height and 1100 mm width. The agglomerator can be used as a particle precharger in a hybrid system or as the first stage in a two-stage electrostatic precipitator, in order to increase their total collection efficiency.